The Development Program for Enhancing Leader Teachers in Schools under the Secondary Educational Service Area Office 32 - ผัดกระโทก, พวงเพชร; หกสุวรรณ, สุทธิพงศ์ (Journal of Roi Et Rajabhat University, 2016)
This research aimed to: 1) study components of teacher leaders in schools under the secondary educational service area office 32 by synthesizing components from related literature review, 6 academicians and validating the conclusions using 5 experts, 2) study current states and method to develop leader teachers in schools under the secondary educational service area office 32 using a questionnaire and a checklist for collecting data from 66 school administrators, 3) develop a program for enhancing teacher leaders in schools under the secondary educational service area office 32 by interviewing 5 experts and drafting the program, and evaluating the propriety and feasibility of a program to develop leader teachers in schools under the secondary educational service area office 32 from 5 experts. The results were as follows: 1. Components of leader teachers in schools under the secondary educational service area office 32, consisted of 5 components: 1) the development of teaching, 2) vision, 3) individual learning, 4) person of transformation, and 5) communication and coordination. 2. The current states of leader teachers in schools under the secondary educational service area office 32 were at the high level in overall and each component. Method development for teacher leaders in schools under the secondary educational service area office 32 according to opinions of school administrators from most to least were self-study, learning on the job, and studying in best practice schools. 3. The program for teacher leaders in schools under the secondary educational service area office 32 verified both propriety and feasibility were at high level.